The Relationship between Family Background and Labor Market Success - Pirohov-Tóth, Barbara; Kiss, Zsuzsanna (International Journal of Engineering and Management Sciences, 2020)
In our study, we undertake to explore the social background of fresh graduates (has absolutorium) by field of study. In doing so, we put great emphasis on the educational attainment of the parents and the financial situation of the family, as these factors can have a significant impact on young people's learning opportunities, attitudes and career paths. In the theoretical part of our research, we consider it important to present the experiences of domestic and international authors on the socio-economic situation. Subsequently, the 2015 Graduate Career Tracking System (DPR) database provided us an excellent opportunity to study the complex data collected by the 34 higher education institutions. In our analysis, we highlighted the different socio-economic backgrounds of graduates from different disciplines. Based on our research, we have concluded that young people from richer families are in a better position on the labor market, earning higher incomes than children of parents with lower social status